Pembuatan dan Pemasangan Petunjuk Arah Jalan untuk Meningkatkan Aksesibilitas Jalan pada Desa Amborgang - Akasia Berutu; Raimond Agustin; Try Septiyando Sinaga; Yamowalo Zega; Jesica Sirait (jurnal ABDIMAS Indonesia, 2025)
Villages are the smallest government structure in the Republic of Indonesia. Amborgang Village is located in an inland area of Porsea Sub-district that is difficult to access using the internet network, so many migrants from outside the village and tourists have difficulty finding road access to the village. The lack of clear road directions causes confusion and difficulty finding important locations of Amborgang Village, such as public facilities, hamlet names, and community service centers. The purpose of this research is to create informative and easy-to-understand road directions to improve accessibility in the village. The method used through qualitative and quantitative approaches, including determining the right location for the installation of the directions, creating an attractive and useful visual design. It also included informing the community about the use and function of the signage. The results of this project show a significant improvement in the ease of navigation to the Village facility center, this can be reviewed after the installation of road directions makes newcomers no longer need to ask questions to Amborgang Village residents.